2004
DOI: 10.1590/s1516-89132004000400016
|View full text |Cite
|
Sign up to set email alerts
|

Total mercury in the night shark, Carcharhinus signatus in the western equatorial Atlantic Ocean

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…It is evident that information regarding tissue distribution of metals in sharks is fragmented, except for Hg presence in muscular tissue. Hg levels quite always high have, in fact, been reported in the muscle of various shark species from marine worldwide (Storelli et al 2001(Storelli et al , 2003(Storelli et al , 2005Adams and McMichael 1999;Ferreira et al 2004;Pinho et al 2002;Turoczy et al 2000;Pethybridge et al 2010). The biological traits of these animals as longevity and slow growth rates, in conjunction with the high trophic status of many shark species, have been invoked to explain the high levels encountered in their meats (Lyle 1984 Windom et al 1973) revealed higher brain levels and comparable skin levels (0.02-0.28 μg g −1 ; Pethybridge et al 2010) with respect to those encountered in the organisms under study.…”
Section: Tissue/organ Distribution Of Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that information regarding tissue distribution of metals in sharks is fragmented, except for Hg presence in muscular tissue. Hg levels quite always high have, in fact, been reported in the muscle of various shark species from marine worldwide (Storelli et al 2001(Storelli et al , 2003(Storelli et al , 2005Adams and McMichael 1999;Ferreira et al 2004;Pinho et al 2002;Turoczy et al 2000;Pethybridge et al 2010). The biological traits of these animals as longevity and slow growth rates, in conjunction with the high trophic status of many shark species, have been invoked to explain the high levels encountered in their meats (Lyle 1984 Windom et al 1973) revealed higher brain levels and comparable skin levels (0.02-0.28 μg g −1 ; Pethybridge et al 2010) with respect to those encountered in the organisms under study.…”
Section: Tissue/organ Distribution Of Concentrationsmentioning
confidence: 99%
“…This, in combination with contaminant inputs originating directly from industrial and urban sources located along the coast, makes this environment particularly interesting from the point view of contamination. Nevertheless, trace metal concentrations in these organisms are not well documented either in the Mediterranean area or in other marine regions, and the few studies concentrate on muscle tissue and/or liver only (Adams and McMichael 1999;Endo et al 2008;Ferreira et al 2004;Gibbs and Miskiewicz 1995;Lacerda et al 2000;Mársico et al 2007;McMeans et al 2007;Pinho et al 2002;Powell and Powell 2001;Serrano et al 1997Serrano et al , 2000Storelli et al 2003;Turoczy et al 2000), without any broader picture of the accumulation processes and distribution of the metals among the other tissues. According to the mechanisms of absorption, regulation, storage, and excretion of metals, the various fish tissues present varying bioaccumulation rates and due to their different roles in the above processes, their analysis lead to results with special interest and interpretation (Catsiki and Strogyloudi 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on Hg levels in fish (e.g. Lacerda et al 2000;Sharma et al 2008;Ferriera et al 2004;Bodaly et al 1997) has found that Hg concentrations should be highest in animals that feed highest on the trophic cascade (i.e., carnivorous/predator species should have the highest Hg levels). Given the potential for Hg contamination in fish, we also wished to examine the local population's awareness regarding Hg contamination and the potential risk of Hg to their health.…”
Section: Study System-the Pairaba Do Sul Watershed and Inhabitantsmentioning
confidence: 97%
“…Varios estudios han demostrado que el mercurio, generalmente presenta una correlación positiva con la talla y edad (Walker et al, 1976, Watling et al, 1981Lacerda et al, 2000;Cadena-Cárdenas, 2004). La longitud o talla de un pez ha sido reconocida como un factor muy importante que influye en los niveles finales de mercurio (Olayinka & Kusemijo, 2006), se considera que los organismos que ocupan posiciones tróficas altas y son especies longevas (lo cual está relacionado a la talla del organismo), son susceptibles a contener altas concentraciones de este tóxico (Gomes et al, 2004). Esto se debe principalmente, a que pueden consumir una gran variedad de presas que tengan concentraciones elevadas de mercurio, y tengan mayor tiempo de exposición al mercurio por su longevidad.…”
Section: Concentración De Metales Y La Longitud De Individuosunclassified